Kekerasan seksual pada anak di bawah umur: Menyoroti dampak dan upaya pencegahan - Nusaputri, Yusriana (Maliki Interdisciplinary Journal, 2024)
Sexual violence against minors is a serious problem that affects millions of children around the world. This study aims to describe the psychological and social impact of sexual violence on children, as well as highlight preventive measures that can be taken to protect children from these risks. In this study, we pooled existing literature on child sexual abuse and analyzed its impact on the mental and emotional health of victims. Common psychological effects include post-traumatic stress disorder, anxiety, depression, behavioral changes, and other mental health problems. In addition, child sexual abuse can also generate social problems such as social isolation, difficulties in establishing healthy interpersonal relationships, and problems with normal functioning in the social environment. We also analyzed various risk factors that can lead to sexual violence among minors. These factors include instability in the family, lack of supervision, ease of access to pornographic material and lack of awareness about the issue of sexual violence against children. It is hoped that this study can provide further information on sexual violence against children and inform prevention efforts undertaken by the community, government and related organizations. Through strong cooperation and appropriate measures, we can ensure a better and safer future for children, where they can grow and develop without fear of becoming victims of sexual violence.